Food web analysis of a tropical wetland ecosystem recently invaded by South American sailfin catfish (Janitor Fish) Pterygoplichthys disjunctivus - Travis, Marianne Hubilla (University of the Philippines Visayas, 2009)
This study examined the food web structure of the Agusan Marsh, a Philippine wetland of international importance, which was recently invaded by the South American sailfin catfish Pterygoplichthysdisjunctivus. Stable carbon and nitrogen isotopes were used to 1) determine the diet and trophic positions of aquatic consumers ; (2) compare the diet and trophic positions of fishes from riverine and lacustrine habitats ; and (3) examine the possibility of dietary and trophic overlap among indigenous fishes, P. disjunctivus, and other fish invaders. C3 plants are the most important primary producers in the Marsh since they support the diet of the majority of aquatic consumers. Many of the consumers also derive their carbon from particulate organic matter (POM) and sediment organic matter (SOM). Fishes demonstrate certain patterns of dietary and trophic level shifts across habitats, which can be linked to resource availability and to their feeding preferences. The overlapping diet and trophic positions of fishes with similar dietary sources suggest potential resource competition. The recent changes in fish species diversity and the reduction of indigenous fish catches in the March therefore, can be attributed to potential resource competition among fish species feeding on the same dietary sources, P. disjunctivus is not the only cause of species displacement in the Marsh. Other exotic fishes also contributed to the problem. However, unlike the other exotic fishes, P. disjunctivus is considered as the most destructive due to its adverse ecological and socioeconomic impacts. Fishery course management coupled with strict regulation of wildlife and aquarium trade laws are needed to prevent the entry of other exotic fishes, and to save the biodiversity of Agusan Marsh.